Sword techniques of Musashi and other samurai masters - Tanaka, Fumon (Kodansha USA, Inc., 2013)
"In his eye-opening new book, author Fumon Tanaka uses the life and accomplishments of sword master Miyamoto Musashi to look at the history of swords and sword fighting, and to discuss their role in Japanese history and in the development of traditional Japanese martial arts systems" -- from Amazon.com